Hadiths on Al-taswir And Ittijahat Al-ulama' Concerning Handmade Image Making - Muhammad Akmalludin Mohd Hamdan; Amar Fettane (IIUM Press, 2024)
Al-Burhan Journal of Qurʾan and Sunnah Studies Volume5, Number2 (page: 63-83)